2023
DOI: 10.1002/jpen.2495
|View full text |Cite
|
Sign up to set email alerts
|

Current practices in nutrition therapy in cardiac surgery patients: An international multicenter observational study

Abstract: Background Cardiac surgery patients with a prolonged stay in the intensive care unit (ICU) are at high risk for acquired malnutrition. Medical nutrition therapy practices for cardiac surgery patients are unknown. The objective of this study is to describe the current nutrition practices in critically ill cardiac surgery patients worldwide. Methods We conducted a prospective observational study in 13 international ICUs involving mechanically ventilated cardiac surgery patients with an ICU stay of at least 72 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A prospective observational study evaluating current medical nutrition practices in cardiac surgery patients (including patients on MCS) illuminated an urgent need to improve MNT in this specific patient cohort [8 ▪ ]. Enteral nutrition (EN) was the predominant nutrition route ( n = 187 [79%] patients) and, on average, initiated with significant delay (45 h [range, 0–277 h] after ICU admission), and a combined regimen of EN and parenteral nutrition (PN), to compensate potential nutritional deficiencies was used in 14% of patients.…”
Section: Current Status Of Medical Nutrition Therapy Practices In Pat...mentioning
confidence: 99%
“…A prospective observational study evaluating current medical nutrition practices in cardiac surgery patients (including patients on MCS) illuminated an urgent need to improve MNT in this specific patient cohort [8 ▪ ]. Enteral nutrition (EN) was the predominant nutrition route ( n = 187 [79%] patients) and, on average, initiated with significant delay (45 h [range, 0–277 h] after ICU admission), and a combined regimen of EN and parenteral nutrition (PN), to compensate potential nutritional deficiencies was used in 14% of patients.…”
Section: Current Status Of Medical Nutrition Therapy Practices In Pat...mentioning
confidence: 99%
“…2,55 In an international and multiinstitutional study, Heyland et al showed that when enteral feeding is started late, 38.8 hours after admission, patients received only 61.2% of calories and 57.6% of protein prescribed, with 74% of patients not meeting at least 80% of their energy target. 61 Undernutrition is particularly present in cardiac surgery 62,63 and in patients subject to esophagectomy. Patients undergoing esophagectomy could remain nutritionally compromised in the months/ years that follow and may never return to baseline.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
“…When considering the metabolism of ICU patients and their confounders, the significant difference between predicted and measured resting energy expenditure (REE) in mechanically ventilated patients is confirmed in recent work [1]. Although guidance is openly available, implementation remains a challenge, as nutritional adequacy (both in energy and protein) varies enormously, as proved by the 'NutritionDay' initiative [2], as well as several other publications, including inadequate feeding in the cardiac surgery subphenotype ICU population [3]. From a patient's perspective, continuity of care seems obvious.…”
Section: Introductionmentioning
confidence: 96%